THE INFLUENCE OF INQUIRY TRAINING LEARNING MODEL ON SCIENCE PROCESS SKILLS USING PhET MEDIA IN SOUND WAVE MATERIALS - Sari, Dwi Finta; Harahap, Mukti Hamjah ((IPER) Indonesian Physics Education Research, 2021)
This study aimed to analyze the effect of inquiry training learning models on science process skills using PhET media on the subject matter of sound wave in class XI semester II at SMA Negeri 14 Medan T.P 2018/2019. This type of research is quasi experimental with Two Group Pretest-Posttest Design. With the cluster random sampling tecnique obtained by class XI IPA-7 as the experimental class and class XI IPA-5 as the control class. The experimental class was treated with the inquiry training learning model using PhET media and the control class with conventional learning. Data collection techniques using essay tests form as much as 10 items which have been validated by the validator. From the results of the study, the average posstest of the experimental class was 76.46 and the control class was 69.27. The results of data analysis using the t test of one party shows a difference namely tcount = 4.314 and ttable = 1.637.  This research was concluded that there was effect of inquiry training learning model on skills of science process using PhET media in sound wave materials.Keywords: Science Process Skills, Inquiry Training Learning Models, Sound Waves